2015
DOI: 10.1111/fwb.12601
|View full text |Cite
|
Sign up to set email alerts
|

The introduced signal crayfish and native noble crayfish have different effects on sublittoral macroinvertebrate assemblages in boreal lakes

Abstract: Summary We investigated differences in the abundance, community composition and taxon richness of sublittoral macroinvertebrates in boreal lakes containing introduced invasive signal crayfish (Pacifastacus leniusculus) or native noble crayfish (Astacus astacus). We hypothesised that sublittoral macroinvertebrate assemblages in lakes containing noble crayfish, which reportedly prefer the shallow littoral, would differ little from those in lakes without crayfish, in contrast to assemblages in lakes containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
2
14
1
Order By: Relevance
“…Even though this contrasts with some previous studies Nilsson et al, 2012;Twardochleb et al, 2013), Ercoli et al (2015) found no differences in littoral benthic macroinvertebrate densities between smaller Finnish lakes with crayfish and without crayfish, suggesting any effect of signal crayfish on overall numerical abundance of littoral benthic macroinvertebrates in boreal lakes is probably weak.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Even though this contrasts with some previous studies Nilsson et al, 2012;Twardochleb et al, 2013), Ercoli et al (2015) found no differences in littoral benthic macroinvertebrate densities between smaller Finnish lakes with crayfish and without crayfish, suggesting any effect of signal crayfish on overall numerical abundance of littoral benthic macroinvertebrates in boreal lakes is probably weak.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this temporal study were generally consistent with our previous findings from largescale spatially replicated space-for-time studies in Lake Päijänne (Bjurström et al, 2010;Ruokonen et al, 2014) and in other boreal lakes Ercoli et al, 2015) The overall mean benthic macroinvertebrate densities were similar at the crayfish and non-crayfish sites throughout the study years 2007−2011, as found previously (Bjurström et al, 2010;Ruokonen et al, 2014). Even though this contrasts with some previous studies Nilsson et al, 2012;Twardochleb et al, 2013), Ercoli et al (2015) found no differences in littoral benthic macroinvertebrate densities between smaller Finnish lakes with crayfish and without crayfish, suggesting any effect of signal crayfish on overall numerical abundance of littoral benthic macroinvertebrates in boreal lakes is probably weak.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Studies documenting the effect of invasive crayfish in stream ecosystems have identified significant reductions in the biomass and richness of aquatic macrophytes Nyström et al, 2001), and aquatic invertebrates Stenroth and Nyström, 2003;Crawford et al, 2006;Nilsson et al, 2012;Ercoli et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%